Economics of Organic Manure Use in Tomatoes Production in Enugu State, Nigeria - Offie, Ndubuisi N.; Enete, Anselm A. (Canadian Journal of Agriculture and Crops, 2020)
The study dwelt on the economics of organic manure use in tomatoes production in Enugu State, Nigeria, using a sample of 120 randomly selected respondents, each from farmers that used organic manure only in tomatoes production and those that combined both organic and chemical fertilizers; making a total of 240 respondents. Questionnaire was administered to get information from the respondents. Data analysis was done using Gross margin and z-statistic. The result indicated that generally tomatoes farming was profitable, but using only organic matter with gross margin of N390, 996/ha/annum (1074.16 USD) was more profitable than combined use of organic manure with chemical fertilizers with gross margin result of N324, 000/ha/annum (890.10 USD). The above result shows that organic manure should not be viewed as something useless rather as an underutilized resource which should be used on the farm to increase farm production.